A genome‐wide association study of prostate cancer in Latinos. Issue 7 (3rd July 2019) - Du, Zhaohui; Hopp, Hannah; Ingles, Sue A.; Huff, Chad; Sheng, Xin; Weaver, Brandi; Stern, Mariana; Hoffmann, Thomas J.; John, Esther M.; Van Den Eeden, Stephen K.; Strom, Sara; Leach, Robin J.; et al.
Abstract : Latinos represent <1% of samples analyzed to date in genome‐wide association studies of cancer. The clinical value of genetic information in guiding personalized medicine in populations of non‐European ancestry will require additional discovery and risk locus characterization efforts across populations. In the present study, we performed a GWAS of prostate cancer (PrCa) in 2, 820 Latino PrCa cases and 5, 293 controls to search for novel PrCa risk loci and to examine the generalizability of known PrCa risk loci in Latino men. We also conducted a genetic admixture‐mapping scan to identify PrCa risk alleles associated with local ancestry. Genome‐wide significant associations were observed with 84 variants all located at the known PrCa risk regions at 8q24 (128.484–128.548) and 10q11.22 ( MSMB gene). In admixture mapping, we observed genome‐wide significant associations with local African ancestry at 8q24. Of the 162 established PrCa risk variants that are common in Latino men, 135 (83.3%) had effects that were directionally consistent as previously reported, among which 55 (34.0%) were statistically significant with p < 0.05. A polygenic risk model of the known PrCa risk variants showed that, compared to men with average risk (25th–75th percentile of the polygenic risk score distribution), men in the top 10% had a 3.19‐fold (95% CI: 2.65, 3.84) increased PrCa risk. In conclusion, we found that the known PrCa risk variants can effectively stratify PrCa risk in Latino men. Larger studies in Latino populations will be required to discover and characterize genetic risk variants for PrCa and improve risk stratification for this population. Abstract : What's new? There is strong evidence for a genetic predisposition to prostate cancer (PrCa). Most of this information has come from European ancestry populations, with Latinos representing less than 1% of samples in cancer genome‐wide association studies (GWAS). In this study, the majority of established PrCa risk variants (83.3%) were consistently associated with PrCa risk in Latinos. A polygenic risk score comprised of GWAS‐identified risk variants could identify 10% of Latino men with a three‐fold increase in PrCa risk. These findings suggest that common germline variants for PrCa can stratify risk in Latino men, which has implications for targeted screening and prevention.